The ability of the Question and Answer (Q&A) Method With the Help of Learnin Videos Against Student Learning Outcomes Amid the Covid-19 Pandemic - M Ikhbal Jaya Putra; M Junaid; Fauzan Sulman (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
In learning physics, it is very necessary to have the ability to understand concepts, especially in the midst of the Covid-19 pandemic. Education must continue to ensure the implementation of the learning process in accordance with their talents and interests and ensure student learning outcomes. The purpose of this research is to contribute to the teacher's contribution in improving the learning outcomes of class VIII Madrasah Tsanawiyah Pondok Pesantren Darul Arifin Jambi using the question and answer method assisted by video learning to improve student learning outcomes. This research is Classroom Action Research (CAR) using 2 cycles. Each cycle has 4 stages, namely planning, implementation, observation and reflection. The subjects in this study were all students of class VIII Madrasah Tsanawiyah Pondok Pesantren Darul Arifin Jambi City. The technique of collecting data is through observation and learning outcomes tests, with a minimum success indicator of 75% of students succeeding in the learning outcomes test. In the learning outcomes test, the average score of students is still low, namely 34.97 with a percentage of completeness of 5.88%, in the first cycle it increases to 63, with a completeness percentage of 52.94%, in the second cycle the average value becomes 76.47 with a completeness percentage of 82.35%